Urban farming: the challenges of hydroponic and vertical farming in Malaysia - Emily Hon Tshin Yapp; Nazarina Jamil; Lilian Shiau Gee Lee; Yew Tzen Chooi; Chee Onn Chen (Cogent Food & Agriculture)
This exploratory study examines the challenges impacting urban farmers in Malaysia, especially those using hydroponic platforms on vertical farms, in three states: Penang, Johor, and Sabah. We adopted a qualitative approach and conducted semi-structured interviews with urban farmers from the three states. Through our interviews, we found these farmers are facing several challenges from government policies and legislative controls, volatile market dynamics, financial constraints, operational limits and environmental factors. This is evident despite the existence of subsidies, price regulations, and other measures intended to protect local farmers. Urban farmers require more efficient and simpler methods for raising capital to sustain operations, facilitate expansion and address prevailing challenges. This study suggests using global financial blockchain networks, agro-tokens, and aggressively expanding agro-lending to help urban farmers, which has been increasing in prominence following Malaysia’s interest in using urban farming to increase crop yields, stabilize food prices, and mitigate food security risks faced by the nation.